2018
DOI: 10.3341/kjo.2017.0051
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course and Prognostic Factors of Acquired Third, Fourth, and Sixth Cranial Nerve Palsy in Korean Patients

Abstract: PurposeThis study aimed to evaluate the clinical course and prognostic factors of acquired third, fourth, and sixth cranial nerve (CN) palsy grouped according to etiology.MethodsThis study involved a retrospective review of the medical records of 153 patients who were diagnosed with acquired paralytic strabismus from January 2004 to July 2015. Outcomes, recovery rates, and time to recovery were investigated according to the affected CN: CN3, CN4, and CN6 palsies. The patients were classified into four groups b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
46
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 18 publications
9
46
2
Order By: Relevance
“…Studies on the etiology of CN6 palsy have reported high frequencies of microvascular disease (28–46%) 3,5,18 or unknown origin (24–31%) 35,10,13,18 . It is widely reported that microvascular diseases are a common cause of isolated unilateral CN6 palsy in patients over 50 years of age 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on the etiology of CN6 palsy have reported high frequencies of microvascular disease (28–46%) 3,5,18 or unknown origin (24–31%) 35,10,13,18 . It is widely reported that microvascular diseases are a common cause of isolated unilateral CN6 palsy in patients over 50 years of age 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Recovery rates of CN6 palsy have been reported as high as 60.0 to 87.3% 3,10,24 . Vascular and idiopathic etiologies were associated with higher natural recovery rates than other etiologies of ocular motor nerve palsies 3,4,9,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In extraocular muscle palsy, CN VI represents the most common type of paralytic strabismus, accounting for 33% to 63% of cases, followed by CN III palsy (22%-41.2%) and CN IV palsy (11%-36%). [1][2][3][4] Isolated medial rectus palsy (MRP) is extremely rare in clinical practice, with only 59 cases being reported in the English literature, often involving single case presentations. [5][6][7][8][9][10][11][12][13][14] Possible aetiologies may include damage of the medial rectus nucleus or terminal branches of the oculomotor nerve serving only the medial rectus, or direct medial rectus muscle injury, such as orbital trauma or surgical complications of endoscopic sinus surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In extraocular muscle palsy, CN VI represents the most common type of paralytic strabismus, accounting for 33% to 63% of cases, followed by CN III palsy (22%‐41.2%) and CN IV palsy (11%‐36%) 1‐4 . Isolated medial rectus palsy (MRP) is extremely rare in clinical practice, with only 59 cases being reported in the English literature, often involving single case presentations 5‐14 .…”
Section: Introductionmentioning
confidence: 99%